PENGARUH KOMPENSASI, LINGKUNGAN KERJA, DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS PEMADAM KEBAKARAN KOTA DEPOK - Prafitri Kumalasari; Sugito Efendi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The Depok City Fire Department has a very important function in carrying out disaster management in the emergency or rescue service, especially firefighting in the Depok area, West Java. Therefore, the performance of the firefighting apparatus is considered very vital in achieving the overall organizational performance of the Fire Department. This study aims to analyse the direct and indirect effects of Compensation, Work Environment, and Leadership on Employee Performance through Job Satisfaction on firefighters at the Depok City Fire Department. This research is quantitative research using an analytical tool in the form of a Structural Equation Model (SEM) program through AMOS software. The data processed were 150 samples from 182 population data. Based on the research results obtained empirical facts in the form of: 1) Compensation directly has a positive effect on employee performance; 2) The environment has a direct positive and insignificant effect on employee performance; 3) Leadership directly has a positive effect on Employee Performance; 4) Direct compensation has a negative effect on Job Satisfaction and is not significant on Job Satisfaction; 5) Environment directly has a negative effect on Job Satisfaction; 6) Leadership directly has a positive effect on Job Satisfaction; 7) Job satisfaction directly has a positive effect on employee performance; 8) Compensation indirectly has a positive effect through Job Satisfaction on Employee Performance; 9) The environment indirectly has a positive effect through Job Satisfaction on Employee Performance; 10) Leadership indirectly has a positive effect through Job Satisfaction on Employee Performance. Therefore, the Depok City Fire Department needs to pay attention to these variables because they have a significant role in improving employee performance.